Targeted delivery of reduced graphene oxide nanosheets using multifunctional ultrasound nanobubbles for visualization and enhanced photothermal therapy - Liu Z; Zhang J; Tian Y; Zhang L; Han X; Wang Q; Cheng W (International Journal of Nanomedicine, 2018)
Zhao Liu,1,* Jia Zhang,2,* Yuhang Tian,1 Lei Zhang,1 Xue Han,1 Qiucheng Wang,1 Wen Cheng1 1Department of Ultrasound, Harbin Medical University Cancer Hospital, Nangang District, Harbin 150080, China; 2Key Laboratory of Microsystems and Microstructure Manufacturing, Ministry of Education, Harbin Institute of Technology, Harbin 150080, China *These authors contributed equally to this work Abstract: Ultrasound molecular imaging as a promising strategy, which involved the use of molecularly targeted contrast agents, combined the advantages of contrast-enhanced ultrasound with the photothermal effect of reduced graphene oxide (rGO). Methods and results: The heparin sulfate proteoglycan glypican-3 (GPC3) is a potential molecular target for hepatocellular carcinoma (HCC). In this study, we covalently linked biotinylated GPC3 antibody to PEGylated nano-rGO to obtain GPC3-modified rGO-PEG (rGO-GPC3), and then combined rGO-GPC3 with avidinylated nanobubbles (NBs) using biotin-avidin system to prepare NBs-GPC3-rGO with photothermal effect and dispersibility, solubility in physiological environment. The average size of NBs-GPC3-rGO complex was 700.4±52.9 nm due to the polymerization of biotin-avidin system. Scanning electron microscope (SEM) showed NBs-GPC3-rGO attached to human hepatocellular carcinoma HepG2 cell. The ultrasound-targeted nanobubble destruction (UTND) technology make use of the physical energy of ultrasound exposure for the improvement of rGO delivery. Compared with other control groups, the highest nanobubble destruction efficiency of NBs-GPC3-rGO was attributed to the dissection effect of rGO on UTND. This is a positive feedback effect that leads to an increase in the concentration of rGO around the HepG2 cell. So NBs-GPC3-rGO using UTND and near-infrared (NIR) irradiation resulted in cell viability within 24 h, 48 h, 72 h lower than other treatment groups. Conclusion: This work established NBs-GPC3-rGO as an ultrasonic photothermal agent due to its suitable size, imaging capability, photothermal efficiency for visual photothermal therapy in vitro. Keywords: reduced graphene oxide, ultrasound-targeted nanobubble destruction, glypican-3, HepG2 cell, photothermal therapy